The impact of online trading on stock market efficiency: What have we learned from the gamestop case? - Arturo Capasso (The Central European Review of Economics and Management (CEREM), 2025)
Aim: To examine the impact of online trading and technological innovations on stock market efficiency, with a focus on the GameStop case as an illustrative example. Research methods: Conceptual and qualitative analysis drawing on the GameStop event, regulatory comparisons between the US and Europe, and a review of literature on electronic trading platforms, financial information dissemination, and social media-driven investor coordination. Findings: Online trading platforms, Web 2.0, and social media have transformed investor behaviour and market dynamics. The GameStop case revealed how coordinated retail investors can challenge traditional market mechanisms and the efficient market hypothesis. The "gamification" of trading apps encourages speculative behaviour and raises concerns about investor risk awareness. Regulatory approaches to short selling differ between the US and Europe, highlighting the need for balanced, internationally coordinated frameworks. Strengthened financial education and updated regulation are essential to mitigate risks while retaining the benefits of technological advances.
Keywords: G14; G18; G23; O33; 330; GameStop case; Online trading; Social media; Stock market efficiency